2021
DOI: 10.1097/md.0000000000026634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic response to coronavirus disease outbreak in a regional emergency medical center

Abstract: Emergency departments (EDs) are on the frontline of the coronavirus disease (COVID-19) outbreak. To resolve the abrupt overloading of COVID-19–suspected patients in a community, each ED needs to respond in various ways. In our hospital, we increased the isolation beds through temporary remodeling and by performing in-hospital COVID-19 polymerase chain reaction testing rather than outsourcing them. The aim of this study was to verify the effects of our response to the newly developed viral outbreak. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…COVID-19 is accompanied by various symptoms; 80% of infected patients have no symptoms or mild symptoms [ 23 ]. Therefore, it is necessary for the emergency department, which is the frontline of hospitals to distinguish suspected infection patients more carefully [ 24 ]. In the current COVID-19 situation, strict screening and careful admission are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is accompanied by various symptoms; 80% of infected patients have no symptoms or mild symptoms [ 23 ]. Therefore, it is necessary for the emergency department, which is the frontline of hospitals to distinguish suspected infection patients more carefully [ 24 ]. In the current COVID-19 situation, strict screening and careful admission are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the crisis, many of them did not feel protected, supported, safe, or prepared. The pandemic has revealed the importance of protecting the mental health and well-being of healthcare professionals in the ED, to respond to any emergency effectively, safely, and with equity at the forefront [38].…”
Section: Discussionmentioning
confidence: 99%
“…2 This caused overcrowding in many EDs and unavailability of hospital beds across the nation. 3 An early triage system is critical for identifying patients with high risk of severe COVID-19 who will require hospitalization. 4 To date, many risk factors have been identified that contribute to the severity of COVID-19, such as advanced age, obesity, and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%